ANALISIS PROGRAM PILOT PROJEK PENGENTASAN KEMISKINAN (STUDI KASUS HIBAH BERGILIR SAPI DESA RANAH BARU KECAMATAN KAMPAR KABUPATEN KAMPAR TAHUN 2015) - Sahdila Rahayu, Zaili Rusli, Achmad Hidir (JIANA ( Jurnal Ilmu Administrasi Negara ), 2020)
Analysis of Pilot Programs for Poverty Alleviation Projects (Case Study of Ranah Baru Cow Turning Grant in Kampar District, Kampar District, 2015).This research is motivated by the implementation of a pilot poverty alleviation program in this case the program of giving cows rotating in the village of Ranah Baru, Kampar District, Kampar Regency. The purpose of this study was to analyze pilot poverty reduction project programs in particular the existing cow rotating program, in this case the Ranah baru village, Kampar District, Kampar Regency and to find out and analyze the factors that influence the success and failure of the cows rotating grant program by the District Government Kampar Kepada Livestock farmer groups located in the Ranah Baru Village, Kampar District, Kampar Regency. This study uses a qualitative descriptive research method approach. Primary data was obtained directly through interviews from key informants, namely the Plantation, Animal Husbandry and Animal Health Service of Kampar Regency, Kampar Regency DPRD Member for the period 2014-2019, the Head of the New Ranah Village, the new Village Field Extension Officer, the Basamo Compact Farmer Group, Desa Ranah Baru, Data secondary obtained from research documents. The results showed that the elements of expansion or communication and coordination between the organizing agencies starting from the Plantation, Animal Husbandry and Animal Health Service, the Village Government to the Livestock Farmers Group supported the successful implementation of the Ranah Baru Cow Rotating Grant Program in Kampar District, Kampar District. successful implementation of the Pilot Project Program Poverty alleviation in this case the grant of rotating cattle in the village of the new Ranah Kampar District of Kampar Regency, Factors that Influence the Success and Failure of the Poverty Reduction Project Program in particular the cow rotating village Ranah Baru Kampar District Kamparantara District Other lack of available resources humans who have the competence to carry out the care and maintenance of cattle, this is due to the lack of willingness to care for and maintain the given cow grants, the quality of their sources of labor has not been adequately trained, influence the level of success and pilot programs of poverty alleviation projects, especially grants taking turns in the village of Ranah Baru, Kampar District, Kampar District.